Undoing epistemic violence in religious leadership in African theological education - Naidoo, Marilyn (Practical Theology, 2023)
Epistemological injustice refers to situations where individuals or groups are systematically excluded from accessing or contributing to knowledge because of their social identities. Theological knowledge and practices have generalised masculine concerns and experiences and space must be made to value women’s knowing to create inclusive, equitable and emancipating practices that is owned and lived out within the institution. This article explores epistemic violence against African women in theological education that limits their possibility of participation, highlighting how women are still denied full recognition. It engages the practical theological task of making a critical analysis of the gender system by identifying specific frameworks of knowledge that validate and legitimise ways of knowing and practices in educational spaces. By critiquing the positioning of women, anti-women frameworks can be deconstructed and reformed. This article offers interventions that must be realised that enable women to reflect and theorise about their lived experiences. Through the process of finding voice women discover their own subjectivity which dislocates labels, and thereby undoes this violence.
paid
Keywords: African context; African culture; Epistemic violence; female ordination; leadership development; theological education